Thermoplastic resin composition and its uses
A thermoplastic resin composition with specific ratios of thermoplastic resin, metal oxide, and unmodified polyolefin wax addresses kneading and hydrophilicity issues, achieving a hard, ceramic-like texture with antibacterial properties and low water absorption.
Patent Information
- Application Number
- JP2023533186
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-03-18
- Filing Date
- 2022-07-07
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2042-07-07
AI Technical Summary
Thermoplastic resin compositions containing inorganic fillers like metal oxides suffer from poor kneading properties and increased hydrophilicity, leading to a moist texture and potential elution of inorganic compounds, which affects the mechanical properties and texture of molded products.
A thermoplastic resin composition comprising 10 to 50 parts by mass of a thermoplastic resin, 50 to 90 parts by mass of a metal oxide, and 0.1 to 20 parts by mass of an unmodified polyolefin wax, with specific thermal conductivity and antibacterial properties, to achieve a hard texture similar to ceramics and low water absorption.
The composition provides a molded product with low water absorption, high thermal conductivity, and a hard texture, mimicking ceramics, while maintaining excellent antibacterial and antiviral properties.
Smart Images

Figure 0007605988000001 
Figure 0007605988000002 
Figure 0007605988000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a thermoplastic resin composition containing a metal oxide and uses thereof. [Background technology]
[0002] Thermoplastic resins such as polyolefins and ABS resins are molded by various methods and are used in a wide range of applications. On the other hand, polyolefins such as polypropylene are inferior in mechanical properties such as heat resistance, rigidity, and tensile strength compared to engineering plastics (engineering plastics) such as polyamide and polycarbonate, so inorganic fillers such as talc, and heat-resistant fibers such as glass fiber and carbon fiber are mixed (added) as reinforcing materials depending on the application.
[0003] For example, Patent Document 1 proposes a polyolefin composition containing a large amount of an inorganic filler made of an inorganic compound, 20 to 80 parts by weight. On the other hand, it has been found that blending a large amount of an inorganic compound such as a metal oxide results in poor kneadability with polyolefins. To improve the kneadability, for example, Patent Document 2 proposes blending 0.1 to 20 parts by mass of a modified polyolefin wax with a composition consisting of 10 to 50 parts by mass of a thermoplastic resin and 50 to 90 parts by mass of a metal oxide. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 52-15542 [Patent Document 2] International Publication No. 2017 / 209215 Summary of the Invention [Problem to be solved by the invention]
[0005] However, it has been found that thermoplastic resin compositions obtained by blending modified polyolefin waxes tend to have a relatively high hydroxyl group density on the surface of the resulting molded article, which makes the article more hydrophilic and gives it a moist texture. It has also been found that under certain conditions (such as acid solutions), this can lead to the elution of inorganic compounds, resulting in a deterioration in texture.
[0006] An object of the present invention is to obtain a thermoplastic resin composition which does not increase hydrophilicity (has low water absorbency) and has a hard texture, and is suitable for obtaining a molded article having a texture closer to that of pottery. [Means for solving the problem]
[0007] The present invention relates to, for example, the following items [1] to
[20] . In this specification, the term "polymer" includes homopolymers and copolymers unless otherwise specified. [1] A thermoplastic resin composition comprising 10 to 50 parts by mass of a thermoplastic resin (A), 50 to 90 parts by mass of a metal oxide (B) (wherein the total amount of (A) + (B) is 100 parts by mass), and 0.1 to 20 parts by mass of an unmodified polyolefin wax (C) relative to 100 parts by mass of the total amount of (A) + (B).
[0008] [2] The thermoplastic resin composition according to [1], wherein the thermoplastic resin (A) is at least one selected from the group consisting of ethylene-based polymers, propylene-based polymers, 1-butene-based polymers, 4-methyl-1-pentene-based polymers, and ABS-based resins. [3] The thermoplastic resin composition according to [1] or [2], wherein the metal oxide (B) includes magnesium oxide. [4] The thermoplastic resin composition according to any one of [1] to [3], wherein the average particle size of the metal oxide (B) is in the range of 0.1 to 110 μm.
[0009] [5] The thermoplastic resin composition according to any one of [1] to [4], wherein the thermal conductivity of the metal oxide (B) is in the range of 10 to 300 W / mK. [6] The thermoplastic resin composition according to any one of [1] to [5], wherein the thermoplastic resin composition has a thermal conductivity in the range of 0.5 to 5 W / mK. [7] The thermoplastic resin composition according to any one of [1] to [6], wherein the specific gravity of the thermoplastic resin composition is in the range of 1.0 to 5.0.
[0010] [8] The thermoplastic resin composition according to any one of [1] to [7], comprising 10 to 30 parts by mass of the thermoplastic resin (A) and 70 to 90 parts by mass of the metal oxide (B) (wherein the total amount of (A) + (B) is 100 parts by mass). [9] The thermoplastic resin composition according to any one of [1] to [8], wherein in an antibacterial test conducted using Escherichia coli in accordance with JIS Z 2801:2012 (film adhesion method), the antibacterial activity value after 24 hours is 2.0 or more under conditions without performing water resistance and light resistance pretreatment.
[0011]
[10] The thermoplastic resin composition according to any one of [1] to [9], wherein in an antibacterial test conducted using Staphylococcus aureus in accordance with JIS Z 2801:2012 (film adhesion method), the antibacterial activity value after 24 hours is 2.0 or more under conditions without performing water resistance and light resistance pretreatment.
[11] The thermoplastic resin composition according to any one of [1] to
[10] , having an antiviral activity value of 2.0 or more in an antiviral test performed using feline calicivirus in accordance with ISO 21702:2019.
[12] The thermoplastic resin composition according to any one of [1] to
[11] , comprising a fibrous filler (D) in an amount of 0.1 to 20 parts by mass per 100 parts by mass of the total of the thermoplastic resin (A) and the metal oxide (B).
[0012]
[13] A molded article comprising the thermoplastic resin composition according to any one of [1] to
[12] .
[14] A door handle, door knob, handrail, or switch comprising the thermoplastic resin composition according to any one of [1] to
[12] .
[15] A housing comprising the thermoplastic resin composition according to any one of [1] to
[12] .
[16] A clothing accessory comprising the thermoplastic resin composition according to any one of [1] to
[12] .
[0013]
[17] A container comprising the thermoplastic resin composition according to any one of [1] to
[12] .
[18] A stationery item comprising the thermoplastic resin composition according to any one of [1] to
[12] .
[19] Tableware or sake cup comprising the thermoplastic resin composition according to any one of [1] to
[12] .
[20] A mouse or keyboard comprising the thermoplastic resin composition according to any one of [1] to
[12] . Effect of the Invention
[0014] The thermoplastic resin composition of the present invention has an extremely low water absorption rate and a thermal conductivity equivalent to that of pottery, so that it has a cool feel to the touch and a hard texture, and is suitable for obtaining molded articles having a texture closer to that of pottery. On the other hand, the product of the present invention has antibacterial properties due to the effect of the metal oxides contained therein, so that it is suitable for obtaining molded articles for applications in which the texture can be felt by direct contact. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The present invention will be specifically described below. <Thermoplastic resin (A)> As the thermoplastic resin (A), which is one of the components contained in the thermoplastic resin composition of the present invention, for example, an olefin-based polymer, an ABS-based resin, a styrene-based resin, a polyester, etc. can be used.
[0016] Olefin polymers are homopolymers of α-olefins (including ethylene) such as ethylene, propylene, 1-butene, and 4-methyl-1-pentene, copolymers of the above α-olefins with other α-olefins, and copolymers of the above α-olefins with monomers other than α-olefins, and are polymers whose main component is an α-olefin. Specific examples of the thermoplastic resin (A) according to the present invention include the following polymers.
[0017] <Ethylene polymer (A1)> The ethylene polymer (A1) according to the present invention is a homopolymer of ethylene or a copolymer of ethylene and an α-olefin having 3 to 20 carbon atoms, and examples of such polymers are those mainly composed of structural units derived from ethylene, which are usually called high density polyethylene (HDPE), medium density polyethylene (MDPE), low density polyethylene (LDPE), linear low density polyethylene (LLDPE), and ethylene-α-olefin copolymers. Specific examples of the α-olefin having 3 to 20 carbon atoms to be copolymerized with ethylene include propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene, 2-methyl-1-butene, 3-methyl-1-butene, 3,3-dimethyl-1-butene, and 3,5,5-trimethyl-1-hexene. Among them, α-olefins having 3 to 10 carbon atoms are preferred, α-olefins having 3 to 8 carbon atoms are more preferred, and in particular, ethylene, 1-butene, 1-hexene, 4-methyl-1-pentene and 1-octene are even more preferred. The molar ratio of ethylene to α-olefin (ethylene / α-olefin) is preferably 99 / 1 to 60 / 40, more preferably 95 / 5 to 70 / 30, and even more preferably 90 / 10 to 60 / 25.
[0018] Specific examples of suitable ethylene-α-olefin copolymers include ethylene-propylene copolymers, ethylene-1-butene copolymers, ethylene-1-hexene copolymers, ethylene-4-methyl-1-pentene copolymers, ethylene-1-octene copolymers, ethylene-propylene-1-butene copolymers, and ethylene-propylene-1-octene copolymers. Among these, ethylene-propylene copolymers, ethylene-1-butene copolymers, ethylene-1-hexene copolymers, ethylene-4-methyl-1-pentene copolymers, and ethylene-1-octene copolymers are preferred, and ethylene-1-butene copolymers are more preferred. The density of the ethylene polymer (A1) (measured according to JIS K7112) is preferably 850 to 980 kg / m 3 , more preferably 855 to 978 kg / m 3 , more preferably 860 to 976 kg / m 3 , particularly preferably 862 to 973 kg / m 3 It is.
[0019] When the thermoplastic resin composition of the present invention contains an ethylene-based polymer (A1), a molded article obtained from the thermoplastic resin composition has higher thermal conductivity, is excellent in hot and cold sensation, and tends to emit a high-pitched sound when struck, compared to a case in which the thermoplastic resin composition contains a propylene-based polymer (A2) described below. Such a molded article can be suitably used for various applications without restrictions, and can be suitably used, for example, as a base material for surface modification by metal deposition.
[0020] <Propylene-based polymer (A2)> The propylene-based polymer (A2) according to the present invention is a polymer mainly composed of structural units derived from propylene, such as a propylene homopolymer (propylene homopolymer: homoPP), a copolymer of propylene with ethylene and / or an α-olefin having 4 to 20 carbon atoms (random copolymer: random PP), or a composition of a propylene homopolymer and an ethylene-propylene copolymer (block copolymer: block PP). Specific examples of the α-olefin in the propylene-α-olefin copolymer include ethylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene, 2-methyl-1-butene, 3-methyl-1-butene, 3,3-dimethyl-1-butene, 3-methyl-1-hexene, and 3,5,5-trimethyl-1-hexene. Among them, ethylene and α-olefins having 4 to 10 carbon atoms are preferred, ethylene and α-olefins having 4 to 8 carbon atoms are more preferred, and in particular, ethylene, 1-butene, 1-hexene, 4-methyl-1-pentene and 1-octene are even more preferred. The molar ratio of propylene to α-olefin (propylene / α-olefin) is preferably 99 / 1 to 60 / 40, more preferably 95 / 5 to 70 / 30, and even more preferably 90 / 10 to 70 / 30.
[0021] Specific examples of suitable propylene-α-olefin copolymers (random PP) include propylene-ethylene copolymers, propylene-1-butene copolymers, propylene-1-hexene copolymers, propylene-4-methyl-1-pentene copolymers, propylene-1-octene copolymers, and propylene-ethylene-1-butene copolymers. Among these, propylene-ethylene copolymers and propylene-1-butene copolymers are preferred, and propylene-ethylene copolymers are particularly preferred.
[0022] In the case of a propylene homopolymer, the melting point is preferably 155 to 170°C, more preferably 158 to 165°C. In the case of a propylene-ethylene random copolymer, the ethylene content of the propylene-ethylene random copolymer is preferably 1.9 to 5.4% by mass, more preferably 2.0 to 4.8% by mass. The crystalline melting point of the propylene-ethylene random copolymer measured by a differential scanning calorimeter (DSC) according to JIS K7121 is preferably usually 130 to 150°C, more preferably 130 to 145°C, particularly preferably 135 to 145°C.
[0023] The density of the propylene polymer (A2) (measured according to JIS K7112) is preferably 850 to 910 kg / m 3 More preferably, it is 875 to 909 kg / m 3 More preferably, it is 890 to 908 kg / m 3 It is. The propylene polymer (A2) according to the present invention may be a propylene polymer containing a fibrous filler (D) such as glass fiber described later. In this case, the density of the propylene polymer containing the fibrous filler (D) (measured according to JIS K7112) is preferably 910 to 1220 kg / m 3 and more preferably 940 to 1200 kg / m 3 , more preferably 970 to 1160 kg / m 3 , particularly preferably 1000 to 1120 kg / m 3 It is.
[0024] The propylene-ethylene block copolymer and the propylene-ethylene random copolymer may be used alone or in combination of two or more kinds of copolymers, for example, in order to adjust the MFR. When the thermoplastic resin composition of the present invention contains the propylene-based polymer (A2), a molded article obtained from the thermoplastic resin composition can be suitably used for various applications without any restrictions. Since the molded article has a thermal conductivity close to that of pottery and a specific gravity equivalent to that of pottery, and is not likely to break when subjected to impact such as being dropped, unlike pottery, and is therefore highly safe, the molded article can be suitably used for applications in which the article will be touched by hand, such as tableware such as cups, containers, and door handles.
[0025] 1-Butene polymer (A3) The 1-butene polymer (A3) according to the present invention is a polymer mainly composed of structural units derived from 1-butene, such as a 1-butene homopolymer (polybutene) and a copolymer of 1-butene with ethylene, propylene and an α-olefin having 5 to 20 carbon atoms (1-butene-α-olefin copolymer).
[0026] <4-Methyl-1-pentene polymer (A4)> The 4-methyl-1-pentene polymer (A4) according to the present invention is a polymer mainly composed of structural units derived from 4-methyl-1-pentene, such as a homopolymer of 4-methyl-1-pentene and a copolymer of 4-methyl-1-pentene and an α-olefin having 2 to 20 carbon atoms (excluding 4-methyl-1-pentene) (4-methyl-1-pentene-α-olefin copolymer).
[0027] Specific examples of the α-olefin in the 4-methyl-1-pentene·α-olefin copolymer include linear α-olefins having 2 to 20 carbon atoms (preferably having 2 to 15 carbon atoms, more preferably having 2 to 10 carbon atoms), such as ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, and 1-eicosene, and branched α-olefins having 5 to 20 carbon atoms (preferably having 5 to 15 carbon atoms), such as 3-methyl-1-butene, 3-methyl-1-pentene, 3-ethyl-1-pentene, 4,4-dimethyl-1-pentene, 4-methyl-1-hexene, 4,4-dimethyl-1-hexene, 4-ethyl-1-hexene, and 3-ethyl-1-hexene. Among these, ethylene, propylene, 1-butene, 1-pentene, 1-hexene, and 1-octene are preferred, and ethylene and propylene are particularly preferred. The α-olefin may be derived from one of these compounds or from two or more of these compounds. The molar ratio of 4-methyl-1-pentene to α-olefin (4-methyl-1-pentene / α-olefin) is preferably from 55 / 45 to 90 / 10, more preferably from 60 / 40 to 86 / 14, and further preferably from 68 / 32 to 85 / 15.
[0028] In one embodiment, the 4-methyl-1-pentene polymer (A4) has a peak temperature of loss tangent (tan δ) measured in a temperature range of -40 to 150°C at a frequency of 10 rad / s (1.6 Hz) of 0°C to 60°C, preferably 10°C to 50°C, more preferably 20°C to 45°C, and particularly preferably 25°C to 44°C. The 4-methyl-1-pentene polymer (A4) has a peak value of tan δ of 0.6 or more and 5.0 or less, preferably 0.7 or more and 4.5 or less, and more preferably 0.8 or more and 3.5 or less.
[0029] Tan δ can be calculated as the ratio of the storage modulus (G') to the loss modulus (G") (G" / G': loss tangent) using the storage modulus (G') and loss modulus (G") obtained during the measurement of dynamic viscoelasticity.
[0030] In the present invention, the temperature at which tan δ reaches a peak value (maximum value) in the range of -40 to 150°C is defined as the temperature at which tan δ reaches a peak value (hereinafter "tan δ peak temperature"), and the value of tan δ at that time is defined as the peak value of tan δ (hereinafter "tan δ peak value"). The peak is considered to be due to the glass transition temperature of the 4-methyl-1-pentene polymer (A4).
[0031] In another embodiment, the 4-methyl-1-pentene polymer (A4) preferably has a tan δ peak temperature of 15°C or more and 45°C or less, which is obtained by performing dynamic viscoelasticity measurement at a frequency of 10 rad / s (1.6 Hz) in a temperature range of -40 to 150°C. Here, in terms of the lower limit of the tan δ peak temperature, the tan δ peak temperature is more preferably 20°C or more, and even more preferably 25°C or more. In an exemplary embodiment of the present invention, the tan δ peak temperature is 40°C or less, but may be higher than 40°C as long as the object of the present invention can be achieved. In a typical embodiment of the present invention, the tan δ peak temperature is more preferably 20°C or more and 45°C or less, and even more preferably 25°C or more and 43°C or less. By setting the tan δ peak temperature in the above temperature range, the value of tan δ at room temperature can be further increased.
[0032] The 4-methyl-1-pentene polymer (A4) has a tan δ peak value of preferably 0.6 to 5.0, more preferably 1.0 to 4.8, even more preferably 1.3 to 4.5, and particularly preferably 1.8 to 4.0, as determined by dynamic viscoelasticity measurement at a frequency of 10 rad / s (1.6 Hz) in a temperature range of -40 to 150°C. By setting the tan δ peak value within the above range, it is possible to change the vibration absorption property, hardness and followability of the material according to the tensile or deformation speed.
[0033] The 4-methyl-1-pentene polymer (A4) has a melting point (Tm) measured by a differential scanning calorimeter (DSC) of preferably 160° C. or lower or not observable, more preferably 140° C. or lower or not observable, and further preferably not observable. By satisfying such requirements, the resin composition of the present invention can be easily kneaded with inorganic substances, and vibration absorption and stress relaxation properties can be improved.
[0034] The intrinsic viscosity [η] of the 4-methyl-1-pentene polymer (A4) measured in decalin at 135° C. is preferably 0.1 dL / g to 5.0 dL / g, more preferably 0.5 dL / g to 4.0 dL / g, and even more preferably 0.5 dL / g to 3.5 dL / g. The 4-methyl-1-pentene polymer (A4) having the intrinsic viscosity [η] in the above range is easy to produce a molded product.
[0035] The intrinsic viscosity [η] of the 4-methyl-1-pentene polymer (A4) can be adjusted to fall within the above range by controlling the molecular weight and polymerization activity through the addition of hydrogen during production by polymerization.
[0036] The above-mentioned intrinsic viscosity [η] can be obtained by calculating the viscosity increase rate ηsp (i.e., ηsp / c) per unit concentration c of each polymer when different amounts of thermoplastic resin composition are dissolved in decalin at 135°C, and using this as the reduced viscosity ηred, and extrapolating ηred so that the unit concentration c of the polymer is zero.
[0037] The ratio of the weight average molecular weight (Mw) to the number average molecular weight (Mn) of the 4-methyl-1-pentene polymer (A4) measured by gel permeation chromatography (GPC) (molecular weight distribution: Mw / Mn) is preferably 1.0 to 3.5, more preferably 1.2 to 3.0, and even more preferably 1.5 to 2.8. The 4-methyl-1-pentene polymer (A4) having the above Mw / Mn range is less susceptible to deterioration in moldability due to low molecular weight and low stereoregularity polymers, and is easy to mold.
[0038] The 4-methyl-1-pentene polymer (A4) has a weight average molecular weight (Mw) measured by gel permeation chromatography (GPC) in terms of polystyrene of preferably 500 or more and 10,000,000 or less, more preferably 1,000 or more and 5,000,000 or less, and even more preferably 1,000 or more and 2,500,000 or less.
[0039] The Mw / Mn and Mw of the 4-methyl-1-pentene polymer (A4) can be adjusted to fall within the above range, for example, by using a metallocene catalyst. The above Mw and Mw / Mn can be determined, for example, by analyzing a chromatogram obtained by measuring at a flow rate of 1.0 ml / min and 140°C using a Waters ALC / GPC 150-C plus type (integrated with a differential refractometer detector) liquid chromatograph, two Tosoh Corporation GMH6-HT columns and two GMH6-HTL columns connected in series, o-dichlorobenzene as the mobile phase medium, and a calibration curve using a standard polystyrene sample.
[0040] The density of the 4-methyl-1-pentene polymer (A4) (measured according to JIS K7112) is preferably 870 to 830 kg / m 3 , more preferably 865 to 830 kg / m 3 , more preferably 855 to 830 kg / m 3 Details of the measurement conditions and the like are as described in the Examples section below. The density can be appropriately changed by the comonomer composition ratio of the 4-methyl-1-pentene polymer (A4), and a polymer (A4) having a density within the above range is advantageous in producing a molded article.
[0041] When the thermoplastic resin composition of the present invention contains the 4-methyl-1-pentene polymer (A4), the molded article obtained from the thermoplastic resin composition can be suitably used for various applications without any restrictions. Such a molded article has excellent flexibility compared to the case containing the propylene polymer (A2), and has the characteristics of being easily bent when touched by the addition of a characteristic of good heat conduction, and is easily able to retain its shape at room temperature.
[0042] <ABS resin (A5)> The ABS resin (A5) according to the present invention is a resin containing not only acrylonitrile-butadiene-styrene copolymer, but also graft copolymers obtained by graft polymerizing monomers including aromatic vinyl and vinyl cyanide onto a rubber component made from a monomer including butadiene, and copolymers produced from other monomers copolymerizable with aromatic vinyl and vinyl cyanide. Here, the rubber component is produced by a conventionally known solution polymerization method, bulk polymerization method, emulsion polymerization method, etc. In addition, the rubber and the above-mentioned graft polymer or the copolymer with this rubber may be produced by any of the conventionally known methods such as solution polymerization method, bulk polymerization method, emulsion polymerization method, etc., and are easily available on the market.
[0043] Specific examples of the ABS resin (A5) include commercially available products such as Clarastic manufactured by Nippon A&L Co., Ltd., TECHNO ABS and UMG ABS manufactured by Techno UMG Co., Ltd., Toyolac manufactured by Toray Industries, Inc., and Denka ABS manufactured by Denka Co., Ltd.
[0044] The density of the ABS resin (A5) (measured according to ISO 1183) is preferably 1000 to 1070 kg / m 3 More preferably, it is 1001 to 1060 kg / m 3 More preferably, it is 1002 to 1050 kg / m 3 It is. The ABS resin (A5) may be used alone or in combination of two or more copolymers, for example, in order to adjust the MFR.
[0045] When the thermoplastic resin composition of the present invention contains an ABS resin (A5), a molded article obtained from the thermoplastic resin composition can be suitably used for various applications without limitation. Since the molded article tends to have superior impact resistance and high surface hardness as compared with a case in which the thermoplastic resin composition contains a propylene-based polymer (A2), the molded article can be suitably used for applications such as trays that are expected to be rubbed, the surface of kitchen counters, desks, bathroom counters, and door handles that require strength.
[0046] <Other thermoplastic resins (A6)> Examples of the thermoplastic resin (A6) other than the above-mentioned (A1) to (A5) include styrene-based resins such as polystyrene, polyesters such as PET, polyamides, and acrylic resins. These other thermoplastic resins (A6) can be produced by known methods, and commercially available products may also be used. The other thermoplastic resins (A6) may be used alone or in combination of two or more.
[0047] Among these thermoplastic resins (A), the olefin polymers (A1) to (A4) and the ABS resin (A5) are preferred, and the ethylene polymer (A1), the propylene polymer (A2), the 4-methyl-1-pentene polymer (A4) and the ABS resin (A5) are more preferred. Two or more types of thermoplastic resins (A) may be used in combination.
[0048] The MFR (ASTM D1238, 230°C, 2.16 kg load) of the thermoplastic resin (A) is preferably 7 to 300 g / 10 min. In terms of the lower limit of the MFR, it is preferably 11 g / 10 min or more, more preferably 13 g / 10 min or more, even more preferably 15 g / 10 min or more, and particularly preferably 18 g / 10 min or more. In terms of the upper limit of the MFR, it is preferably 200 g / 10 min or less, more preferably 150 g / 10 min or less, and even more preferably 100 g / 10 min or less. The thermoplastic resin (A) having an MFR within the above range has good moldability such as injection moldability, and the obtained molded article also has good mechanical properties.
[0049] When the thermoplastic resin (A) is a 4-methyl-1-pentene polymer (A4), the upper limit of the MFR (ASTM D1238, 230°C, 2.16 kg load) is preferably 50 g / 10 min or less, more preferably 30 g / 10 min or less, even more preferably 15 g / 10 min or less, and particularly preferably 13 g / 10 min or less.
[0050] When the thermoplastic resin (A) is an ethylene-based polymer (A1), the MFR (ASTM D1238, 190°C, 2.16 kg load) is preferably 6 to 100 g / 10 min. In terms of the lower limit of the MFR, it is preferably 8 g / 10 min or more, more preferably 10 g / 10 min or more, and even more preferably 11 g / 10 min or more. In terms of the upper limit of the MFR, it is preferably 80 g / 10 min or less, more preferably 60 g / 10 min or less, and even more preferably 50 g / 10 min or less.
[0051] When the thermoplastic resin (A) is ABS resin (A5), the MVR (ASTM D1133, 220°C, 10 kg load) is 10 to 100 cm 3 / 10 minutes is preferable. Looking at the lower limit of MVR, 18 cm 3 / 10 minutes or more is preferable, 30cm 3 / 10 minutes or more is preferable, and 40 cm 3 It is more preferable that the MVR is 10 minutes or more. 3 / 10 minutes or less is preferable, 90cm 3 / 10 minutes or less is preferable, and 85 cm 3 It is even more preferable that the time is 10 minutes or less.
[0052] <Metal oxide (B)> The metal oxide (B), which is one of the components contained in the thermoplastic resin composition of the present invention, is not particularly limited in type as long as it is a metal oxide, but it may be a metal oxide having a higher thermal conductivity than the thermoplastic resin (A). For example, metal oxides such as magnesium oxide (45 to 60 W / mK), aluminum oxide (17 to 36.0 W / mK), zinc oxide (25 to 54 W / mK), and titanium oxide (8.4 W / mK) can be used. Two or more kinds of metal oxides may be used in combination. The numerical value in parentheses after the name of the substance indicates the thermal conductivity value at 300 K.
[0053] The metal oxide (B) according to the present invention is preferably a metal oxide having a thermal conductivity in the range of 10 to 300 W / mK. The lower limit of the thermal conductivity is more preferably 15 W / mK, further preferably 20 W / mK, particularly preferably 30 W / mK, and most preferably 40 W / mK.
[0054] The upper limit of the thermal conductivity is more preferably 250 W / mK, further preferably 200 W / mK, and particularly preferably 100 W / mK. By using a metal oxide (B) having a thermal conductivity within the above range, the thermoplastic resin composition obtained by mixing it with the thermoplastic resin (A) has an appropriate thermal conductivity, so that a molded article such as a container can be obtained that feels cool to the touch and feels warm when hot food is placed inside.
[0055] Unlike the case where titanium oxide is used as a photocatalyst, in applications where light irradiation is not required and antibacterial and / or antiviral properties are required, the metal oxide (B) is preferably magnesium oxide or zinc oxide, and more preferably magnesium oxide because it is white in color, easy to color, and inexpensive.
[0056] The metal oxide (B) according to the present invention may have a spherical, cubic, plate-like, columnar, hexagonal plate-like shape, etc., of which the spherical shape is preferred. The metal oxide (B) may also be pulverized.
[0057] The metal oxide (B) according to the present invention preferably has an average particle size in the range of 0.1 to 110 μm. The lower limit of the average particle size is more preferably 0.2 μm, further preferably 0.5 μm, and particularly preferably 1 μm.
[0058] The upper limit of the average particle size is more preferably 105 μm, further preferably 90 μm, and particularly preferably 85 μm. If the average particle size is too small, the particles may be easily aggregated, which may lead to poor handling and difficulty in uniformly mixing with the thermoplastic resin (A). On the other hand, if the average particle size is too large, the thermal conductivity of the resulting thermoplastic resin composition may be too low, and the mechanical properties of the resulting molded article may be deteriorated.
[0059] In applications requiring higher thermal conductivity, it is preferable to use, for example, a metal oxide (b1) having an average particle size of 0.1 μm or more and less than 10 μm and a metal oxide (b2) having an average particle size of 10 μm or more and 110 μm or less in combination. In this case, the blending ratio (mass ratio) is, for example, preferably (b1) / (b2)=1 / 99 to 49 / 51, more preferably 5 / 95 to 45 / 55, and even more preferably 10 / 90 to 40 / 60.
[0060] By using a metal oxide (b1) having a small average particle size in combination with a metal oxide (b2) having a large average particle size, the metal oxide (b1) fills the gaps between the metal oxide (b2) and the packing density increases, thereby improving the thermal conductivity of the resulting thermoplastic resin composition.
[0061] Moreover, the metal oxide (B) preferably has a small aspect ratio from the viewpoint of uniformity of heat conduction, etc. Specifically, the aspect ratio is preferably less than 1.2, more preferably less than 1.1.
[0062] The metal oxide (B) according to the present invention is preferably treated to be water-resistant. The metal oxide (B) preferably does not substantially contain metal hydroxides and hydrates thereof or hydrates of metal oxides. Specifically, the content of metal hydroxides and hydrates thereof or hydrates of metal oxides in 100% by mass of the entire metal oxide (B) is preferably 1% by mass or less, more preferably 0.5% by mass or less, and particularly preferably 0.3% by mass or less.
[0063] <Unmodified polyolefin wax (C)> The unmodified polyolefin wax (C), which is one of the components contained in the thermoplastic resin composition of the present invention, is a low molecular weight polymer and is not particularly limited as long as it is an unmodified wax made of a polyolefin such as polyethylene wax or polypropylene wax, but polyethylene wax and polypropylene wax are preferred, and polyethylene wax is more preferred.
[0064] The unmodified polyolefin wax (C) according to the present invention is unmodified and has not been modified by oxidation or with an unsaturated carboxylic acid or the like. The unmodified polyolefin wax (C) according to the present invention preferably has an acid value measured in accordance with JIS K0070 of 0.01 mgKOH / g or less, more preferably 0 mgKOH / g.
[0065] <Polyethylene wax> The polyethylene wax used as the unmodified polyolefin wax (C) according to the present invention is a wax made of an ethylene homopolymer, or a copolymer of ethylene and an α-olefin, etc. As the α-olefin, an α-olefin having 3 to 10 carbon atoms is preferable, an α-olefin having 3 to 8 carbon atoms is more preferable, and 1-butene is further preferable.
[0066] The polyethylene wax according to the present invention preferably has a density of 890 to 980 kg / m as measured in accordance with the density gradient tube method of JIS K7112 (1999). 3 More preferably, it is in the range of 895 to 975 kg / m 3 When the density of the polyethylene wax falls within this range, the dispersibility of the polyethylene wax in the thermoplastic resin composition is improved.
[0067] The polyethylene wax according to the present invention preferably has a number average molecular weight of 700 to 4,000, more preferably 1,500 to 3,800, in terms of standard polyethylene, as measured by gel permeation chromatography.
[0068] The polyethylene wax having a number average molecular weight (Mn) of 700 to 4000 can be dispersed more appropriately in the thermoplastic resin (A) when the thermoplastic resin composition of the present invention is molded, and also contributes to the dispersibility of the metal oxide (B). It can also reduce the extrusion load during molding / extrusion. As a result, the productivity of the molded product can be improved.
[0069] The polyethylene wax according to the present invention preferably has a weight average molecular weight (Mw) of 1,000 to 9,000, more preferably 1,500 to 8,000, and even more preferably 2,000 to 7,000, in terms of standard polyethylene, as measured by gel permeation chromatography.
[0070] The polyethylene wax according to the present invention has a melting point of preferably 70 to 130°C, and more preferably 80 to 129°C. The melting point of the polyethylene wax was measured by a differential scanning calorimeter (DSC) in accordance with JIS K7121.
[0071] <Polypropylene wax> The polypropylene wax used as the unmodified polyolefin wax (C) according to the present invention is a wax made of a propylene homopolymer, or a copolymer of propylene with ethylene or an α-olefin, etc. As the α-olefin, an α-olefin having 4 to 10 carbon atoms is preferable, an α-olefin having 4 to 8 carbon atoms is more preferable, and 1-butene is further preferable.
[0072] 《Thermoplastic resin composition》 The thermoplastic resin composition of the present invention is a composition containing 10 to 50 parts by mass of the thermoplastic resin (A), 50 to 90 parts by mass of the metal oxide (B) (wherein the total amount of (A) + (B) is 100 parts by mass), and 0.1 to 20 parts by mass of the unmodified polyolefin wax (C) relative to 100 parts by mass of the total amount of (A) + (B).
[0073] The lower limit of the content of the thermoplastic resin (A) in the thermoplastic resin composition of the present invention is preferably 12 parts by mass, more preferably 16 parts by mass, and further preferably 20 parts by mass. When the content of the thermoplastic resin (A) in the thermoplastic resin composition is a certain amount or more, existing molding methods such as injection molding can be performed.
[0074] The upper limit of the content of the thermoplastic resin (A) is preferably 45 parts by mass, more preferably 40 parts by mass, and further preferably 36 parts by mass. When the content of the thermoplastic resin (A) in the thermoplastic resin composition of the present invention is a certain amount or less, the thermal conductivity of the resulting thermoplastic resin composition is sufficiently exhibited, and the resulting molded article has a sense of weight and texture.
[0075] On the other hand, the lower limit of the content of the metal oxide (B) is preferably 55 parts by mass, more preferably 60 parts by mass, and further preferably 68 parts by mass. The upper limit of the content of the metal oxide (B) is preferably 88 parts by mass, more preferably 84 parts by mass, and further preferably 80 parts by mass.
[0076] In applications requiring antibacterial and / or antiviral properties, the lower limit of the content of the metal oxide (B) is preferably 70 parts by mass, more preferably 72 parts by mass, and even more preferably 74 parts by mass or more. Naturally, the upper limit of the content of the thermoplastic resin (A) is preferably 30 parts by mass, more preferably 28 parts by mass, and even more preferably 26 parts by mass or less.
[0077] When the amounts of the thermoplastic resin (A) and the metal oxide (B) are within the above ranges, a molded article having good moldability and antibacterial and / or antiviral properties can be obtained. The thermoplastic resin composition of the present invention contains 0.1 to 20 parts by mass of the unmodified polyolefin wax (C) when the total of the thermoplastic resin (A) and the metal oxide (B) is 100 parts by mass. The lower limit of the content of the unmodified polyolefin wax (C) is preferably 0.2 parts by mass, more preferably 0.4 parts by mass, and further preferably 0.5 parts by mass.
[0078] The upper limit of the content of the unmodified polyolefin wax (C) is preferably 15 parts by mass, more preferably 10 parts by mass, and further preferably 5 parts by mass. The thermoplastic resin composition of the present invention contains the unmodified polyolefin wax (C) in the above range, which can improve kneadability when obtaining the thermoplastic resin composition and when molding the thermoplastic resin composition by reducing the molding torque. In addition, the wax has a lower melting temperature than the thermoplastic resin (A), and therefore acts as a lubricant to prevent wear of the screw and cylinder.
[0079] On the other hand, since the thermoplastic resin composition of the present invention does not contain modified polyolefin wax, there is no risk of unpleasant odor being generated during molding processing. Furthermore, the molded article obtained from the thermoplastic resin composition of the present invention containing the unmodified polyolefin wax (C) has a harder texture and a texture closer to that of pottery than the molded article obtained from a composition containing a modified polyolefin wax, and since there is no change in hydrophilicity, there is no risk of metal oxide elution or deterioration in texture.
[0080] The thermoplastic resin composition of the present invention preferably has a specific gravity in the range of 1.0 to 5.0. The thermoplastic resin composition of the present invention more preferably has a lower limit of the specific gravity of 1.2, even more preferably 1.4, and particularly preferably 1.6. The upper limit of the specific gravity is more preferably 4.0, even more preferably 3.0, and particularly preferably 2.5.
[0081] When the specific gravity is within the above range, a molded article having a better texture can be obtained. The thermoplastic resin composition of the present invention preferably has a thermal conductivity in the range of 0.5 to 5 W / mK. The thermoplastic resin composition of the present invention preferably has a lower limit of thermal conductivity of 0.6 W / mK, more preferably 0.65 W / mK, and particularly preferably 0.7 W / mK. The upper limit of thermal conductivity is more preferably 4.5 W / mK, more preferably 4.0 W / mK, and particularly preferably 3.6 W / mK.
[0082] When the thermal conductivity satisfies the above range, a molded article such as a container can be obtained that feels cool to the touch and has a better texture. The thermoplastic resin composition of the present invention preferably has an antibacterial activity value of 2.0 or more using Escherichia coli or Staphylococcus aureus, more preferably an antibacterial activity value of 2.0 or more using Escherichia coli and Staphylococcus aureus. The antibacterial activity value of the thermoplastic resin composition of the present invention can be increased, for example, by increasing the content of metal oxide (B) (e.g., magnesium oxide). An antibacterial activity value of 2.0 or more is considered to have an antibacterial effect. A higher antibacterial activity value is preferable because it indicates a higher antibacterial effect, and there is no particular upper limit.
[0083] The antibacterial activity value in the present invention is an index value based on the test method in JIS Z 2801:2012 "Film adhesion method".
[0084] The thermoplastic resin composition of the present invention preferably has an antiviral activity value of 2.0 or more using feline calicivirus. An antiviral activity value of 2.0 or more is considered to have an antiviral effect. A larger antiviral activity value is preferable because it indicates a higher antiviral effect, and there is no particular upper limit. The antiviral activity value in the present invention is an index value in accordance with the test method in ISO 21702:2019 "Determination of antiviral activity of plastic and other non-porous surfaces."
[0085] The thermoplastic resin composition of the present invention may contain a fibrous filler (D) in addition to the unmodified polyolefin wax (C).
[0086] <Fibrous filler (D)> The fibrous filler (D) according to the present invention is a fibrous filler, and specific examples thereof include glass fiber, carbon fiber, magnesium sulfate fiber, polyester fiber, nylon fiber, kenaf fiber, bamboo fiber, jute fiber, and inorganic crystalline whisker fiber. Among these, glass fiber and carbon fiber are preferred.
[0087] When the thermoplastic resin composition of the present invention contains the fibrous filler (D), the mechanical properties such as strength of the resulting molded article are improved. When the thermoplastic resin composition of the present invention contains a fibrous filler (D), it is contained in a range of 0.1 to 20 parts by mass relative to 100 parts by mass of the total amount of the thermoplastic resin (A) and the metal oxide (B). The lower limit of the content of the fibrous filler (D) is preferably 0.2 parts by mass, more preferably 0.3 parts by mass. The upper limit of the content of the fibrous filler (D) is preferably 15 parts by mass, more preferably 10 parts by mass, and even more preferably 8 parts by mass.
[0088] The thermoplastic resin composition of the present invention may contain a filler other than the fibrous filler (D) within a range that does not impair the effects of the present invention. Examples of such fillers include inorganic fillers such as talc, mica, calcium carbonate, ammonium phosphates, silicates, carbonates, and carbon black; and organic fillers such as wood flour, cellulose, rice flour, starch, and corn starch.
[0089] In addition to the above-mentioned fibrous filler (D), the thermoplastic resin composition of the present invention may contain various known additives depending on the application, such as plasticizers, lubricants, antioxidants, UV absorbers, heat stabilizers, pigments, pigment masterbatches, dyes, antistatic agents, flame retardants, coupling agents, and dispersants, within the scope of the present invention.
[0090] <Method for producing thermoplastic resin composition> The thermoplastic resin composition of the present invention can be obtained by mixing the above-mentioned components using a dry blend, a Henschel mixer, a Banbury mixer, a kneader, or the like, or by mixing and then melt-kneading the components using a single-screw extruder, a twin-screw extruder, a high-speed twin-screw extruder, or the like.
[0091] <Molded body> The thermoplastic resin composition of the present invention has excellent moldability and can be used in various molding methods. Specific examples of molded articles obtained from the thermoplastic resin composition of the present invention include injection molded articles, foam molded articles, injection foam molded articles, extrusion molded articles, blown molded articles, vacuum / pressure molded articles, calendar molded articles, stretched films, and inflation films.
[0092] More specifically, examples of ceramic products include containers for food, tableware such as forks, knives, spoons, plates, teapots, and teacups, sake bottles and choshi sake bottles, and cutlery rests such as chopstick rests. These products can be easily molded by injection molding, and are very useful as tableware, sake bottles, containers, and cutlery that can replace ceramics because they are easy to feel the hot and cold of the contents and have a sense of weight. In addition, ceramics can be used for other purposes, such as daily necessities such as lampshades and vases, housings and structural materials for certain audio speakers (high-end speakers, etc.), water-related products such as washbasins and toilets, and vases and pots for holding plants. In addition to the uses of ceramics, by taking advantage of the characteristic of being able to give a sense of weight and stability, ceramics can be used for models and toys such as plastic models, furniture such as desks and chairs, home appliances such as refrigerators, rice cookers, and vacuum cleaners, musical instruments such as piano keys, tiles, artificial marble substitutes, building materials, and clothing accessories such as buttons. It may also be suitable as a filament for 3D printers, taking advantage of its hot and cold sensation and moldability.
[0093] Other examples of the molded article of the present invention include containers such as various bottles and jars that take advantage of the characteristics such as designability, stability, antibacterial properties and texture, steering wheels and shift knobs for vehicles and ships, door handles and door knobs, various switches, handrails, mice, keyboards, controllers, decorative accessories, stationery, smartphone covers, tablet covers, PC / tablet housings, book covers, and other uses that are commonly touched by the hands.
[0094] Suitable examples of containers are those for beauty-related products such as cosmetics (such as cosmetic liquids and cosmetic creams), shampoos (including body shampoos), and conditioners, for which these performances tend to have a large impact on the commercial value. More specifically, examples of containers include containers with lids (including airless containers), (cosmetic) compacts, (cosmetic) palettes, bottles, and other shapes.
[0095] In recent years, plastic containers such as polyolefin, which are lightweight and have excellent impact resistance, have been used in most cases for such applications, but these materials are not suitable for creating a sense of luxury in terms of sight, touch (including thermal conductivity, weight, etc.) etc. Containers such as ceramics are suitable for creating a sense of luxury, but these have major problems such as limited freedom in terms of design and mass production, and low impact resistance.
[0096] The containers of the present invention can be produced using the same molding methods as conventional plastic products, and therefore not only are they excellent in productivity and design, but they also have superior impact resistance compared to ceramics and the same weight and thermal conductivity as ceramics, making them suitable for the above-mentioned applications.
[0097] Furthermore, the molded article obtained from the thermoplastic resin composition of the present invention is also useful as a heat dissipation member in applications requiring high thermal conductivity. For example, it is very useful as a heat dissipation member such as a heat dissipation sheet in various electronic devices such as electronic components requiring high thermal conductivity, notebook computers and mobile devices. In addition, if the thermoplastic resin composition of the present invention is applied to a part or all of the housing of various electronic devices such as notebook computers and mobile devices and used in combination with a heat dissipation sheet, it is expected that the heat dissipation performance of the electronic device can be further improved. Furthermore, it is also possible to manufacture a housing that can reduce the possibility of developing low-temperature burns during long-term operation by using the thermoplastic resin composition of the present invention for a part of the housing of various electronic devices such as notebook computers and mobile devices, and using a material with a reduced metal oxide content or a material that does not contain metal oxide for the other parts, such as parts that are often touched by hands during operation. Such a housing can be manufactured, for example, by installing multiple resin injection gates in a mold for molding the housing and injecting resins of different compositions into each gate.
[0098] As for other applications, it is also useful as a substitute for metal housings, taking advantage of its excellent thermal conductivity, freedom of shape during molding, high impact strength, etc. For example, it is expected to be used in the housings and belts of watches and wristwatches, furniture parts (e.g. metal handles), and exterior materials for home appliances such as washing machines and refrigerators. EXAMPLES
[0099] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples as long as it does not deviate from the gist of the invention. The materials used in the examples are as follows. The methods for evaluating the various physical properties are described below.
[0100] The thermoplastic resins (A) used in the examples and comparative examples are shown below. (1) Thermoplastic resin (A) (1-1) Propylene-based polymer (A2-1): Propylene-ethylene block copolymer (manufactured by Prime Polymer Co., Ltd., trade name X860, MFR (230°C, load 2.16 kg) = 60 g / 10 min, density = 900 kg / m3 , amount of xylene solubles at 25°C = 24% by mass, intrinsic viscosity [η] of the xylene solubles at 25°C = 2.5 dl / g, ethylene content of the xylene solubles at 25°C = 30% by mass. (1-2) Propylene-based polymer (A2-2): Propylene-ethylene block copolymer (manufactured by Prime Polymer Co., Ltd., trade name J-6083HP, MFR (230°C, load 2.16 kg) = 60 g / 10 min, density = 900 kg / m 3 ). (1-3) Propylene-based polymer (A2-3): Short fiber glass-reinforced polypropylene (Prime Polymer Co., Ltd., Prime Polypro (registered trademark) V7100, glass fiber content = 20 wt%, MFR (230 °C, load 2.16 kg) = 18 g / 10 min, density = 1030 kg / m 3 ). (1-4) Ethylene-based polymer (A1-1): High-density polyethylene (manufactured by Prime Polymer Co., Ltd., Hi-Zex (registered trademark) product name 1300J, MFR (190°C, load 2.16 kg) = 13 g / 10 min, density = 967 kg / m 3 ). (1-5) Ethylene-based polymer (A1-2): High-density polyethylene (manufactured by Prime Polymer Co., Ltd., Hi-Zex (registered trademark) product name 1700J, MFR (190°C, load 2.16 kg) = 16 g / 10 min, MFR (230°C, load 2.16 kg) = 28 g / 10 min, density = 967 kg / m 3 ). (1-6) Ethylene-based polymer (A1-3): Ethylene-1-butene copolymer (manufactured by Mitsui Chemicals, Inc., TAFMER (registered trademark), product name A-35070S, MFR (190°C, load 2.16 kg) = 35 g / 10 min, MFR (230°C, load 2.16 kg) = 65 g / 10 min, density = 870 kg / m 3 ). (1-7) Propylene-based polymer (A2-4): Propylene homopolymer (manufactured by Prime Polymer Co., Ltd., trade name J13B, MFR (230°C, load 2.16 kg) = 200 g / 10 min, density = 890 kg / m 3 ). (1-8) 4-Methyl-1-pentene polymer (A4-1): The 4-methyl-1-pentene-propylene copolymer used was prepared by the method described below. (1-9) ABS resin (A5-1): ABS resin (manufactured by Nippon A&L Co., Ltd., product name GA-704, MVR (220°C, load 10 kg) = 62 cm 3 / 10min, MFR(230℃, load 5kg)=39.8g / 10min, MFR(230℃, load 2.16kg)=13g / 10min, density 1040kg / m 3 )
[0101] [Method for producing 4-methyl-1-pentene polymer (A4-1)] Into a 1.5 L stainless steel autoclave equipped with an agitator and thoroughly purged with nitrogen, 300 ml of n-hexane (dried over activated alumina under a dry nitrogen atmosphere) and 450 ml of 4-methyl-1-pentene were placed at 23° C. Into this autoclave, 0.75 ml of a 1.0 mmol / ml toluene solution of triisobutylaluminum (TIBAL) was placed, and the agitator was turned on.
[0102] Next, the autoclave was heated until the internal temperature reached 60° C., and pressurized with propylene to a total pressure (gauge pressure) of 0.40 MPa. Next, 0.34 ml of a toluene solution containing 1 mmol of methylaluminoxane (calculated as Al) and 0.01 mmol of diphenylmethylene(1-ethyl-3-t-butyl-cyclopentadienyl)(2,7-di-t-butyl-fluorenyl)zirconium dichloride, which had been prepared in advance, was pressed into the autoclave with nitrogen to initiate the polymerization reaction. During the polymerization reaction, the temperature inside the autoclave was adjusted to 60°C.
[0103] 60 minutes after the start of polymerization, 5 ml of methanol was injected into the autoclave with nitrogen to terminate the polymerization reaction, and the pressure inside the autoclave was then reduced to atmospheric pressure. After the pressure was reduced, acetone was added to the reaction solution while stirring the reaction solution, to obtain a polymerization reaction product containing the solvent.
[0104] Next, the obtained polymerization reaction product containing the solvent was dried at 100° C. under reduced pressure for 12 hours to obtain 36.9 g of a powdery 4-methyl-1-pentene polymer (A4-1).
[0105] The 4-methyl-1-pentene polymer (A4-1) had a 4-methyl-1-pentene content of 72.5 mol % and a propylene content of 27.5 mol %. The physical properties of the 4-methyl-1-pentene polymer (A4-1) are as follows: Density is 839kg / m 3 The intrinsic viscosity [η] was 1.5 dl / g, the weight average molecular weight (Mw) was 337,000, the molecular weight distribution (Mw / Mn) was 2.1, the melt flow rate (MFR; 230°C, 2.16 kg load) was 11 g / 10 min, and no melting point (Tm) was observed. The peak temperature of tan δ was 30°C, and the peak value was 2.78.
[0106] The MFR and density of each of the thermoplastic resins (A) were measured by the following methods. [Melt flow rate (MFR) (g / 10 min)] In accordance with ASTM D1238, measurements were performed at a temperature of 190°C and a load of 2.16 kg, at a temperature of 230°C and a load of 2.16 kg, or at a temperature of 230°C and a load of 5 kg. 〔density〕 Measurement was performed according to JIS K 7112.
[0107] [Composition of 4-methyl-1-pentene polymer (A4-1)] The content (mol%) of each structural unit (4-methyl-1-pentene and α-olefin) in the 4-methyl-1-pentene polymer (A4-1) is 13 Measurements were performed by C-NMR. Measurement equipment: Nuclear magnetic resonance equipment (ECP500, manufactured by JEOL Ltd.) Observation core: 13 C(125MHz) Sequence: Single pulse proton decoupling Pulse width: 4.7μsec (45° pulse) Repeat time: 5.5 seconds -Number of times: 10,000 or more Solvent: orthodichlorobenzene / deuterated benzene (volume ratio: 80 / 20) mixed solvent Sample concentration: 55mg / 0.6mL ·Measurement temperature: 120℃ Chemical shift reference value: 27.50 ppm
[0108] [Intrinsic viscosity [η] of 4-methyl-1-pentene polymer (A4-1)] The intrinsic viscosity [η] was measured at 135° C. in a decalin solvent using an Ubbelohde viscometer as a measuring device. Approximately 20 mg of a specific 4-methyl-1-pentene copolymer is dissolved in 25 ml of decalin, and then the specific viscosity ηsp is measured using an Ubbelohde viscometer in an oil bath at 135°C. After diluting this decalin solution by adding 5 ml of decalin, the specific viscosity ηsp is measured in the same manner as above. This dilution procedure is repeated two more times, and the value of ηsp / C when the concentration (C) is extrapolated to 0 is calculated as the limiting viscosity [η] (unit: dl / g) (see formula 1 below). [η]=lim(ηsp / C) (C→0)...Equation 1
[0109] [Weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn) of 4-methyl-1-pentene polymer (A4-1)] The weight average molecular weight (Mw) and the molecular weight distribution (Mw / Mn) expressed as the ratio of the weight average molecular weight (Mw) to the number average molecular weight (Mn) were calculated by a standard polystyrene conversion method using gel permeation chromatography (GPC). -conditions- Measurement equipment: GPC (ALC / GPC 150-C plus type, differential refractometer detector integrated type, Waters) Column: Two GMH6-HT (Tosoh Corporation) and two GMH6-HTL (Tosoh Corporation) connected in series Eluent: o-dichlorobenzene Column temperature: 140℃ Flow rate: 1.0mL / min
[0110] [Melting point (Tm) of 4-methyl-1-pentene polymer (A4-1)] The melting point (Tm) was measured using a differential scanning calorimeter (DSC220C, manufactured by Seiko Instruments Inc.) as a measuring device. Approximately 5 mg of the polymer was sealed in an aluminum pan for measurement and heated from room temperature to 200°C at 10°C / min. In order to completely melt the polymer, it was held at 200°C for 5 minutes and then cooled to -50°C at 10°C / min. After being left at -50°C for 5 minutes, it was heated a second time to 200°C at 10°C / min, and the peak temperature (°C) in this second heating was taken as the melting point (Tm) of the polymer. Note that when multiple peaks were detected, the peak detected on the highest temperature side was adopted.
[0111] [Dynamic viscoelasticity of 4-methyl-1-pentene polymer (A4-1)] In the measurement of dynamic viscoelasticity, a 3 mm thick pressed sheet made of the resin to be measured was used as the measurement sample, and a 45 mm x 10 mm x 3 mm strip was cut out as required for the dynamic viscoelasticity measurement. Using an ANTON Paar MCR301, the temperature dependence of dynamic viscoelasticity was measured from -40 to 150°C at a frequency of 10 rad / s (1.6 Hz), and the temperature at which the loss tangent (tan δ) due to the glass transition temperature reached its peak value (maximum value) in the range of 0 to 40°C (hereinafter also referred to as the "peak value temperature") and the value of the loss tangent (tan δ) at that time were measured.
[0112] The metal oxides (B) used in the examples and comparative examples are shown below. (2) Metal oxides (B) (2-1) Magnesium oxide (B-1): MgO (Kyowa Chemical Industry Co., Ltd., PyroXuma 5301, average particle size = 2 μm). (2-2) Magnesium oxide (B-2): MgO (Kyowa Chemical Industry Co., Ltd., PyroXuma 3320, average particle size = 20 μm). (2-3) Magnesium oxide (B-3): Magnesium oxide that had been treated as described below was used. Magnesium oxide (B-3) having an average particle size of about 60 to 80 μm was obtained by sieving MgO (DENMAG KMAO-H (average particle size = 45 to 355 μm) manufactured by Tateho Chemical Industries Co., Ltd.) through a 180-250 mesh sieve.
[0113] The unmodified polyolefin waxes (C) used in the examples and comparative examples are shown below. (3) Unmodified polyolefin wax (C) (3-1) Unmodified polyolefin wax (C-1): Ethylene-1-butene copolymer (manufactured by Mitsui Chemicals, Inc., product name Excelex 30050B, density = 907 kg / m 3 , acid value = 0 mg KOH / g, melting point = 91°C, weight average molecular weight = 5100, molecular weight distribution Mw / Mn = 2.6).
[0114] (4) Modified polyolefin wax (4-1) Modified polyolefin wax: modified polyolefin polymer (manufactured by Mitsui Chemicals, Inc., trade name Excelex 15341PA, density = 930 kg / m 3 , acid value = 14 mg KOH / g, melting point = 89°C).
[0115] The physical properties of the thermoplastic resin compositions obtained in the examples and comparative examples were measured by the following methods. 〔specific gravity〕 The specific gravity was measured by comparing it relative to the density of water at 4°C using the underwater displacement method. [Melt flow rate (MFR) (g / 10 min)] In accordance with ASTM D1238, measurements were performed at a temperature of 230°C and a load of 2.16 kg or at a temperature of 230°C and a load of 5 kg.
[0116] [Pencil hardness] Pencil hardness was measured with a test load of 750 g. (Thermal conductivity (W / m K) The thermal conductivity was measured by a constant information heat flow meter method, specifically, using a measuring instrument GH-1 manufactured by ULVAC-RIKO, in accordance with ASTM E1530 at a temperature of 30°C.
[0117] [Head deflection temperature measurement (℃)] According to ISO75-2 Method A, the test was performed using a test piece (2mm x 10mm x 80mm) under the conditions of a heating rate of 120℃ / hour, a test start temperature of 35℃, and a bending stress of 1.8MPaG. HDT was measured using a fully automatic HDT tester 6A-2 (manufactured by Toyo Seiki Co., Ltd.).
[0118] [Water absorption rate (weight %)] Water absorption measurements were carried out at 23°C for 24 hours.
[0119] [Antibacterial activity value (-)] The test was carried out in accordance with the JIS Z 2801:2012 "Film Adhesion Method" test method, and the antibacterial activity value was calculated using the following formula. "Antibacterial activity value" = "Common logarithm of the number of viable bacteria in a blank sample 24 hours after inoculation with E. coli or Staphylococcus aureus" - "Common logarithm of the number of viable bacteria in a test specimen 24 hours after inoculation with E. coli or Staphylococcus aureus" The test strains used in this study are shown below. Antibacterial activity value (Escherichia coli): Escherichia coli NBRC 3972 Antibacterial activity value (Staphylococcus aureus): Staphylococcus aureus NBRC 12732
[0120] [Antiviral activity value (-)] The antiviral activity value of the thermoplastic resin composition was determined in accordance with the test method in ISO 21702:2019. Specifically, a 50 mm square sample was placed in a sterile petri dish, and 0.4 mL of virus liquid was inoculated onto the sample. Then, a coating film was placed on the sample. After the petri dish was covered, the sample and virus were inoculated for 24 hours under conditions of a temperature of 25°C and humidity of 90% or more. The virus was collected from the sample, and the virus infectivity was measured by the plaque method, and the antiviral activity value was calculated using the following formula. "Antiviral activity value" = "Common logarithm value [Ut] of the virus infectivity of the blank sample 24 hours after inoculation with the virus" - "Common logarithm value [At] of the test specimen 24 hours after inoculation with the virus" The viruses used in this test are shown below. Feline calicivirus: ATCC VR-782
[0121] (1) Antibacterial properties (water resistance category 0 and light resistance category 0: no light resistance or water resistance pretreatment) For water resistance category 0 and light resistance category 0, the "film adhesion method" test was conducted on samples that had not undergone the water resistance and light resistance pretreatment described in "Antibacterial Product Technology Council Test Method Durability Test Method (2020 Edition) (1) Water Resistance Test" and "Antibacterial Product Technology Council Test Method Durability Test Method (2020 Edition) (2) Light Resistance Test", and the antibacterial activity value was calculated. In pretreatment, on the assumption that the performance of antibacterial or antiviral products will be reduced by contact with water or exposure to light, samples are treated under the test conditions (water temperature, immersion time, or light source exposure time) specified for each category.
[0122] (2) Durability of antibacterial properties (water resistance category 1 and water resistance category 2) For water resistance category 1 and water resistance category 2, tests were conducted using pretreated samples according to the "Film Adhesion Method" in accordance with the "Antibacterial Product Technology Council Test Method: Durability Test Method (2020 Edition) (1) Water Resistance Test," and antibacterial activity values were calculated.
[0123] (3) Durability of antibacterial properties (light resistance category 1 and light resistance category 2) For light resistance category 1 and light resistance category 2, tests were conducted using pretreated samples according to the "Film Adhesion Method" in accordance with the "Antibacterial Product Technology Council Test Method: Durability Test Method (2020 Edition) (2) Light Resistance Test," and antibacterial activity values were calculated.
[0124] Example 1 30 parts by mass of propylene polymer (A2-1), 70 parts by mass of magnesium oxide (B-1), and 0.6 parts by mass of unmodified polyolefin wax (C-1) were kneaded using a kneading device (a tabletop kneader (manufactured by Irie Shokai)) at 200°C and 15 to 35 rpm to obtain a thermoplastic resin composition. The obtained pellets of the thermoplastic resin composition were pressed into a sheet at 200°C using a manual hydraulic heating press (manufactured by Imoto Seisakusho) to obtain a sample for physical property testing. The obtained sheet was used to measure the physical properties by the above-mentioned method. The results are shown in Table 1.
[0125] Example 2 A sample for physical property test was prepared in the same manner as in Example 1, except that 23 parts by mass of a propylene-based polymer (A2-2), 2.0 parts by mass of an ethylene-based polymer (A1-3), 75 parts by mass of magnesium oxide (B-2), and 0.6 parts by mass of an unmodified polyolefin-based wax (C-1) were used instead of the raw materials of the thermoplastic resin composition used in Example 1. The physical properties were measured by the methods described above. In addition, antibacterial activity durability tests in water resistance category 0 and light resistance category 0 were performed by the methods described above. The results are shown in Table 1.
[0126] Furthermore, antibacterial and antiviral activity persistence tests in water resistance category 1, water resistance category 2, light resistance category 1 and light resistance category 2 were carried out by the method described above. The results of the antibacterial activity persistence test in water resistance categories 1 and 2 and light resistance categories 1 and 2 are shown in Table 2, and the results of the antiviral activity persistence test in water resistance categories 1 and 2 and light resistance categories 1 and 2 are shown in Table 3.
[0127] Example 3 The same procedure as in Example 1 was repeated to prepare a sample for physical property testing, except that the raw materials for the thermoplastic resin composition were replaced with 23 parts by mass of a propylene-based polymer (A2-2), 2.0 parts by mass of an ethylene-based polymer (A1-3), 15 parts by mass of magnesium oxide (B-1), 60 parts by mass of magnesium oxide (B-2), and 0.6 parts by mass of an unmodified polyolefin wax (C-1) instead of the raw materials used in Example 1. The physical properties of the sample were measured by the methods described above. The results are shown in Table 1.
[0128] Example 4 The same procedure as in Example 1 was repeated to prepare a sample for physical property testing, except that the raw materials for the thermoplastic resin composition were replaced with 23 parts by mass of a propylene-based polymer (A2-2), 2.0 parts by mass of an ethylene-based polymer (A1-3), 22.5 parts by mass of magnesium oxide (B-1), 52.5 parts by mass of magnesium oxide (B-2), and 0.6 parts by mass of an unmodified polyolefin-based wax (C-1) instead of the raw materials used in Example 1. The physical properties of the sample were measured by the methods described above. The results are shown in Table 1.
[0129] Example 5 The same procedure as in Example 1 was carried out except that the raw materials for the thermoplastic resin composition were replaced with 24.5 parts by mass of a propylene-based polymer (A2-2), 0.5 parts by mass of an ethylene-based polymer (A1-3), 75 parts by mass of magnesium oxide (B-2), and 0.6 parts by mass of an unmodified polyolefin-based wax (C-1), and a sample for physical property testing was prepared and the physical properties were measured by the methods described above. The results are shown in Table 1.
[0130] Example 6 The same procedure as in Example 1 was carried out except that the raw materials for the thermoplastic resin composition were replaced with 29.5 parts by mass of a propylene-based polymer (A2-2), 0.5 parts by mass of an ethylene-based polymer (A1-3), 70 parts by mass of magnesium oxide (B-2), and 0.6 parts by mass of an unmodified polyolefin-based wax (C-1), and a sample for physical property testing was prepared and the physical properties were measured by the methods described above. The results are shown in Table 1.
[0131] Example 7 A sample for physical property test was prepared in the same manner as in Example 1, except that 34.5 parts by mass of a propylene-based polymer (A2-2), 0.5 parts by mass of an ethylene-based polymer (A1-3), 65 parts by mass of magnesium oxide (B-2), and 0.6 parts by mass of an unmodified polyolefin-based wax (C-1) were used instead of the raw materials of the thermoplastic resin composition used in Example 1. The physical properties were measured by the methods described above. In addition, antibacterial activity durability tests in water resistance category 0 and light resistance category 0 were performed by the methods described above. The results are shown in Table 1.
[0132] Example 8 The same procedure as in Example 1 was carried out except that the raw materials for the thermoplastic resin composition were replaced with 23 parts by mass of a propylene-based polymer (A2-3), 2.0 parts by mass of an ethylene-based polymer (A1-3), 75 parts by mass of magnesium oxide (B-2), and 0.6 parts by mass of an unmodified polyolefin-based wax (C-1), and a sample for physical property testing was prepared and the physical properties were measured by the methods described above. The results are shown in Table 1.
[0133] As mentioned above, the propylene polymer (A2-3) contains 20% by mass of glass fiber. When the total amount of the propylene polymer (A2-3) excluding the glass fiber (PP portion) and the magnesium oxide (B-2) is set to 100 parts by mass, the compounding ratio is as follows: 19.3 parts by mass of the PP portion of the propylene polymer (A2-3), 2.1 parts by mass of the ethylene polymer (A1-3), 78.6 parts by mass of the magnesium oxide (B-2), 0.6 parts by mass of the unmodified polyolefin wax (C-1), and 4.8 parts by mass of the glass fiber portion of the propylene polymer (A2-3).
[0134] Example 9 The thermoplastic resin composition was prepared in the same manner as in Example 1, except that 11.5 parts by mass of a propylene-based polymer (A2-2), 11.5 parts by mass of a propylene-based polymer (A2-3), 2.0 parts by mass of an ethylene-based polymer (A1-3), 75 parts by mass of magnesium oxide (B-2), and 0.6 parts by mass of an unmodified polyolefin wax (C-1) were used instead of the raw materials used in Example 1. A physical property test sample was prepared and the physical properties were measured by the methods described above. The results are shown in Table 1.
[0135] As mentioned above, the propylene polymer (A2-3) contains 20% by mass of glass fiber. When the total amount of the propylene polymer (A2-3) excluding the glass fiber (PP portion), the propylene polymer (A2-2) and the magnesium oxide (B-2) is set to 100 parts by mass, the compounding ratio is as follows: 11.8 parts by mass of the propylene polymer (A2-2), 9.4 parts by mass of the PP portion of the propylene polymer (A2-3), 2.0 parts by mass of the ethylene polymer (A1-3), 76.8 parts by mass of the magnesium oxide (B-2), 0.6 parts by mass of the unmodified polyolefin wax (C-1), 2.4 parts by mass of the glass fiber portion of the propylene polymer (A2-3).
[0136] Example 10 The same procedure as in Example 1 was repeated except that the raw materials for the thermoplastic resin composition were replaced with 15.3 parts by mass of a propylene-based polymer (A2-2), 7.7 parts by mass of a propylene-based polymer (A2-3), 2.0 parts by mass of an ethylene-based polymer (A1-3), 75 parts by mass of magnesium oxide (B-2), and 0.6 parts by mass of an unmodified polyolefin wax (C-1). A physical property test sample was prepared in the same manner as in Example 1, and the physical properties were measured by the methods described above. The results are shown in Table 1.
[0137] As mentioned above, the propylene polymer (A2-3) contains 20% by mass of glass fiber. When the total amount of the propylene polymer (A2-3) excluding the glass fiber (PP portion), the propylene polymer (A2-2) and the magnesium oxide (B-2) is set to 100 parts by mass, the compounding ratio is as follows: 15.5 parts by mass of the propylene polymer (A2-2), 6.3 parts by mass of the PP portion of the propylene polymer (A2-3), 2.0 parts by mass of the ethylene polymer (A1-3), 76.2 parts by mass of the magnesium oxide (B-2), 0.6 parts by mass of the unmodified polyolefin wax (C-1), 1.6 parts by mass of the glass fiber portion of the propylene polymer (A2-3).
[0138] Example 11 The same procedure as in Example 1 was carried out except that the raw materials for the thermoplastic resin composition were changed to 25 parts by mass of an ethylene polymer (A1-1), 22.5 parts by mass of magnesium oxide (B-1), 52.5 parts by mass of magnesium oxide (B-2), and 0.6 parts by mass of an unmodified polyolefin wax (C-1), and the like, and samples for physical property testing were prepared and the physical properties were measured by the methods described above. The results are shown in Table 1.
[0139] Example 12 The same procedure as in Example 1 was carried out, except that the raw materials for the thermoplastic resin composition were replaced with 25 parts by mass of an ethylene polymer (A1-1), 75 parts by mass of magnesium oxide (B-2), and 0.6 parts by mass of an unmodified polyolefin wax (C-1), and the like, and samples for physical property testing were prepared and the physical properties were measured by the methods described above. The results are shown in Table 1.
[0140] Example 13 The same procedure as in Example 1 was carried out except that the raw materials for the thermoplastic resin composition were changed to 33 parts by mass of an ethylene-based polymer (A1-1), 2.0 parts by mass of an ethylene-based polymer (A1-3), 65 parts by mass of magnesium oxide (B-2), and 0.6 parts by mass of an unmodified polyolefin wax (C-1), and the like, and samples for physical property tests were prepared and the physical properties were measured by the methods described above. The results are shown in Table 1.
[0141] Example 14 The same procedure as in Example 1 was carried out except that the raw materials for the thermoplastic resin composition were changed to the raw materials used in Example 1, and 18 parts by mass of an ethylene-based polymer (A1-1), 2.0 parts by mass of an ethylene-based polymer (A1-3), 80 parts by mass of magnesium oxide (B-2), and 0.6 parts by mass of an unmodified polyolefin wax (C-1) were used. A sample for physical property testing was prepared in the same manner as in Example 1, and the physical properties were measured by the methods described above. The results are shown in Table 1.
[0142] Example 15 The same procedure as in Example 1 was carried out except that the raw materials for the thermoplastic resin composition were replaced with 25 parts by mass of an ethylene polymer (A1-2), 75 parts by mass of magnesium oxide (B-2), and 0.6 parts by mass of an unmodified polyolefin wax (C-1), and the like, and samples for physical property testing were prepared and the physical properties were measured by the methods described above. The results are shown in Table 1.
[0143] Example 16 A sample for physical property testing was prepared in the same manner as in Example 1, except that 23 parts by mass of an ethylene polymer (A1-2), 2.0 parts by mass of an ethylene polymer (A1-3), 75 parts by mass of magnesium oxide (B-2), and 0.6 parts by mass of an unmodified polyolefin wax (C-1) were used instead of the raw materials of the thermoplastic resin composition used in Example 1. The physical properties were measured by the methods described above. In addition, antibacterial activity durability tests in water resistance category 0 and light resistance category 0 were performed by the methods described above. The results are shown in Table 1.
[0144] Example 17 The same procedure as in Example 1 was repeated to prepare a sample for physical property testing, except that the raw materials for the thermoplastic resin composition were changed to those used in Example 1, and 23 parts by mass of an ethylene-based polymer (A1-2), 2.0 parts by mass of an ethylene-based polymer (A1-3), 75 parts by mass of magnesium oxide (B-2), 0.6 parts by mass of an unmodified polyolefin wax (C-1), and 1.0 part by mass of carbon black were used. The physical properties of the sample were measured by the methods described above. The results are shown in Table 1.
[0145] Example 18 The same procedure as in Example 1 was carried out except that the raw materials for the thermoplastic resin composition were replaced with 28 parts by mass of a propylene-based polymer (A2-2), 2.0 parts by mass of an ethylene-based polymer (A1-3), 70 parts by mass of magnesium oxide (B-3), and 0.6 parts by mass of an unmodified polyolefin-based wax (C-1), and a sample for physical property testing was prepared and the physical properties were measured by the methods described above. The results are shown in Table 1.
[0146] Example 19 The same procedure as in Example 1 was repeated to prepare a sample for physical property testing, except that the raw materials for the thermoplastic resin composition were replaced with 28 parts by mass of a propylene-based polymer (A2-2), 2.0 parts by mass of an ethylene-based polymer (A1-3), 70 parts by mass of magnesium oxide (B-3), and 1 part by mass of an unmodified polyolefin-based wax (C-1) instead of the raw materials used in Example 1. The physical properties of the sample were measured by the methods described above. The results are shown in Table 1.
[0147] Example 20 The same procedure as in Example 1 was carried out except that the raw materials for the thermoplastic resin composition were replaced with 28 parts by mass of a propylene-based polymer (A2-2), 2.0 parts by mass of an ethylene-based polymer (A1-3), 70 parts by mass of magnesium oxide (B-3), and 2 parts by mass of an unmodified polyolefin-based wax (C-1), and a sample for physical property testing was prepared and the physical properties were measured by the methods described above. The results are shown in Table 1.
[0148] Example 21 The same procedure as in Example 1 was carried out except that the raw materials for the thermoplastic resin composition were replaced with 23 parts by mass of a propylene-based polymer (A2-2), 2.0 parts by mass of an ethylene-based polymer (A1-3), 75 parts by mass of magnesium oxide (B-3), and 0.6 parts by mass of an unmodified polyolefin-based wax (C-1), and a sample for physical property testing was prepared and the physical properties were measured by the methods described above. The results are shown in Table 1.
[0149] Example 22 The same procedure as in Example 1 was repeated to prepare a sample for physical property testing, except that the raw materials for the thermoplastic resin composition were changed to those used in Example 1, and 14 parts by mass of a propylene-based polymer (A2-2), 14 parts by mass of a propylene-based polymer (A2-4), 2.0 parts by mass of an ethylene-based polymer (A1-3), 70 parts by mass of magnesium oxide (B-2), and 0.6 parts by mass of an unmodified polyolefin-based wax (C-1) were used. The physical properties of the sample were measured by the methods described above. The results are shown in Table 1.
[0150] Example 23 The same procedure as in Example 1 was repeated to prepare a sample for physical property testing, except that the raw materials for the thermoplastic resin composition were replaced with 18.7 parts by mass of a propylene-based polymer (A2-2), 9.3 parts by mass of a propylene-based polymer (A2-3), 2.0 parts by mass of an ethylene-based polymer (A1-3), 70 parts by mass of magnesium oxide (B-2), and 0.6 parts by mass of an unmodified polyolefin wax (C-1) in place of the raw materials used in Example 1. The physical properties of the sample were measured by the methods described above. The results are shown in Table 1.
[0151] As mentioned above, the propylene polymer (A2-3) contains 20% by mass of glass fiber. When the total amount of the propylene polymer (A2-3) excluding the glass fiber (PP portion), the propylene polymer (A2-2) and the magnesium oxide (B-2) is set to 100 parts by mass, the compounding ratio is as follows: 19.1 parts by mass of the propylene polymer (A2-2), 7.6 parts by mass of the PP portion of the propylene polymer (A2-3), 2.0 parts by mass of the ethylene polymer (A1-3), 71.3 parts by mass of the magnesium oxide (B-2), 0.6 parts by mass of the unmodified polyolefin wax (C-1), 1.9 parts by mass of the glass fiber portion of the propylene polymer (A2-3).
[0152] Example 24 The thermoplastic resin composition was prepared in the same manner as in Example 1, except that 11.5 parts by mass of a propylene-based polymer (A2-3), 11.5 parts by mass of a propylene-based polymer (A2-4), 2.0 parts by mass of an ethylene-based polymer (A1-3), 75 parts by mass of magnesium oxide (B-2), and 0.6 parts by mass of an unmodified polyolefin wax (C-1) were used instead of the raw materials used in Example 1. A physical property test sample was prepared and the physical properties were measured by the methods described above. The results are shown in Table 1.
[0153] As mentioned above, the propylene polymer (A2-3) contains 20% by mass of glass fiber. When the total amount of the propylene polymer (A2-3) excluding the glass fiber (PP portion), the propylene polymer (A2-4) and the magnesium oxide (B-2) is set to 100 parts by mass, the compounding ratio is as follows: 9.4 parts by mass of the PP portion of the propylene polymer (A2-3), 11.8 parts by mass of the propylene polymer (A2-4), 2.0 parts by mass of the ethylene polymer (A1-3), 76.8 parts by mass of the magnesium oxide (B-2), 0.6 parts by mass of the unmodified polyolefin wax (C-1), and 2.4 parts by mass of the glass fiber portion of the propylene polymer (A2-3).
[0154] Example 25 The same procedure as in Example 1 was repeated to prepare a sample for physical property testing, except that the raw materials for the thermoplastic resin composition were changed to those used in Example 1, and 14 parts by mass of a propylene-based polymer (A2-3), 14 parts by mass of a propylene-based polymer (A2-4), 2.0 parts by mass of an ethylene-based polymer (A1-3), 70 parts by mass of magnesium oxide (B-2), and 0.6 parts by mass of an unmodified polyolefin-based wax (C-1) were used. The physical properties of the sample were measured by the methods described above. The results are shown in Table 1.
[0155] As mentioned above, the propylene polymer (A2-3) contains 20% by mass of glass fiber. When the total amount of the propylene polymer (A2-3) excluding the glass fiber (PP portion), the propylene polymer (A2-4) and the magnesium oxide (B-2) is set to 100 parts by mass, the compounding ratio is as follows: 11.5 parts by mass of the PP portion of the propylene polymer (A2-3), 14.4 parts by mass of the propylene polymer (A2-4), 2.1 parts by mass of the ethylene polymer (A1-3), 72 parts by mass of the magnesium oxide (B-2), 0.6 parts by mass of the unmodified polyolefin wax (C-1), and 2.9 parts by mass of the glass fiber portion of the propylene polymer (A2-3).
[0156] Example 26 The same procedure as in Example 1 was repeated to prepare a sample for physical property testing, except that the raw materials for the thermoplastic resin composition were changed to those used in Example 1, and 14 parts by mass of a propylene-based polymer (A2-3), 14 parts by mass of a propylene-based polymer (A2-4), 2.0 parts by mass of an ethylene-based polymer (A1-3), 70 parts by mass of magnesium oxide (B-2), and 1.0 part by mass of an unmodified polyolefin wax (C-1) were used. The physical properties of the sample were measured by the methods described above. The results are shown in Table 1.
[0157] As mentioned above, the propylene polymer (A2-3) contains 20% by mass of glass fiber. When the total amount of the propylene polymer (A2-3) excluding the glass fiber (PP portion), the propylene polymer (A2-4) and the magnesium oxide (B-2) is set to 100 parts by mass, the compounding ratio is as follows: 11.5 parts by mass of the PP portion of the propylene polymer (A2-3), 14.4 parts by mass of the propylene polymer (A2-4), 2.1 parts by mass of the ethylene polymer (A1-3), 72 parts by mass of the magnesium oxide (B-2), 1.0 part by mass of the unmodified polyolefin wax (C-1), and 2.9 parts by mass of the glass fiber portion of the propylene polymer (A2-3).
[0158] Example 27 The same procedure as in Example 1 was carried out except that the raw materials for the thermoplastic resin composition were changed to 33 parts by mass of an ethylene-based polymer (A1-2), 2.0 parts by mass of an ethylene-based polymer (A1-3), 65 parts by mass of magnesium oxide (B-2), and 0.6 parts by mass of an unmodified polyolefin wax (C-1), and the like, and samples for physical property tests were prepared and the physical properties were measured by the methods described above. The results are shown in Table 1.
[0159] Example 28 The same procedure as in Example 1 was carried out except that the raw materials for the thermoplastic resin composition were replaced with 35.0 parts by mass of 4-methyl-1-pentene polymer (A4-1), 65 parts by mass of magnesium oxide (B-2), and 0.6 parts by mass of unmodified polyolefin wax (C-1), and a sample for physical property testing was prepared and the physical properties were measured by the methods described above. The results are shown in Table 1.
[0160] Example 29 A sample for physical property testing was prepared in the same manner as in Example 1, except that the raw materials of the thermoplastic resin composition were replaced with 30 parts by mass of 4-methyl-1-pentene polymer (A4-1), 70 parts by mass of magnesium oxide (B-2), and 0.6 parts by mass of unmodified polyolefin wax (C-1) instead of the raw materials used in Example 1. In addition, antibacterial activity durability tests in water resistance category 0 and light resistance category 0 were carried out by the method described above. The results are shown in Table 1.
[0161] Example 30 The same procedure as in Example 1 was carried out except that the raw materials for the thermoplastic resin composition were replaced with 25 parts by mass of 4-methyl-1-pentene polymer (A4-1), 75 parts by mass of magnesium oxide (B-2), and 0.6 parts by mass of unmodified polyolefin wax (C-1), and a sample for physical property testing was prepared and the physical properties were measured by the methods described above. The results are shown in Table 1.
[0162] Example 31 The same procedure as in Example 1 was carried out, except that the raw materials for the thermoplastic resin composition were replaced with 35 parts by mass of ABS resin (A5-1), 65 parts by mass of magnesium oxide (B-2), and 0.6 parts by mass of unmodified polyolefin wax (C-1), and the physical properties of the samples were measured by the methods described above. The results are shown in Table 1.
[0163] Example 32 The same procedure as in Example 1 was carried out, except that the raw materials for the thermoplastic resin composition were replaced with 30 parts by mass of ABS resin (A5-1), 70 parts by mass of magnesium oxide (B-2), and 0.6 parts by mass of unmodified polyolefin wax (C-1), and the physical properties of the samples were measured by the methods described above. The results are shown in Table 1. Furthermore, antibacterial activity persistence tests in water resistance category 0 and light resistance category 0 were carried out by the method described above.
[0164] Example 33 A sample for physical property testing was prepared in the same manner as in Example 1, except that the raw materials for the thermoplastic resin composition were replaced with 25 parts by mass of ABS resin (A5-1), 75 parts by mass of magnesium oxide (B-2), and 0.6 parts by mass of unmodified polyolefin wax (C-1) instead of the raw materials used in Example 1. The results are shown in Table 1.
[0165] Comparative Example 1 The same procedure as in Example 1 was carried out except that the raw materials for the thermoplastic resin composition were replaced with 68 parts by mass of a propylene-based polymer (A2-2), 2.0 parts by mass of an ethylene-based polymer (A1-3), 30 parts by mass of magnesium oxide (B-2), and 0.6 parts by mass of an unmodified polyolefin-based wax (C-1), and a sample for physical property testing was prepared and the physical properties were measured by the methods described above. The results are shown in Table 1. The composition obtained in Comparative Example 1 does not transmit heat well due to its low thermal conductivity, and therefore does not have the luxurious feel of pottery.
[0166] Comparative Example 2 The same procedure as in Example 1 was carried out except that the raw materials for the thermoplastic resin composition were replaced with 23 parts by mass of a propylene-based polymer (A2-2), 2.0 parts by mass of an ethylene-based polymer (A1-3), 75 parts by mass of magnesium oxide (B-2), and 0.6 parts by mass of a modified polyolefin-based wax, and a sample for physical property testing was prepared and the physical properties were measured by the methods described above. The results are shown in Table 1. The composition obtained in Comparative Example 2 had a lower deflection temperature under load and deteriorated physical properties. This is believed to be because the hydrogen bonds with the metal oxide (hereinafter also referred to as filler) are weak due to the low acid value of the modified polyolefin wax, and the filler does not disperse uniformly in the resin. On the other hand, the unmodified polyolefin wax (C) used in the examples has an acid value of 0, so the hydrogen bonds with the filler are weak, but the interaction in the small amount of resin acting as a binder is strong, so the deflection temperature under load and physical properties of the obtained composition are believed to be good.
[0167] Comparative Example 3 The same procedure as in Example 1 was carried out except that the raw materials for the thermoplastic resin composition were changed to 23 parts by mass of a propylene-based polymer (A2-2), 2.0 parts by mass of an ethylene-based polymer (A1-3), and 75 parts by mass of magnesium oxide (B-2), and a sample for physical property testing was prepared and the physical properties were measured by the methods described above. The results are shown in Table 1. The composition obtained in Comparative Example 3 did not contain the unmodified polyolefin wax (C), so the filler was prone to agglomeration and was difficult to disperse uniformly, making it difficult to manufacture and prone to unevenness, resulting in poor kneadability and resin fluidity (MFR).
[0168] [Table 1-1]
[0169] [Table 1-2]
[0170] [Table 1-3]
[0171] In addition, "*1" in Table 1 (Example 21) indicates that the thermoplastic resin composition flowed too much to be measured.
[0172] [Table 2]
[0173] [Table 3]
Claims
1. The composition contains 10 to 40 parts by mass of a thermoplastic resin (A), 60 to 90 parts by mass of a metal oxide (B) (wherein the total amount of (A) + (B) is 100 parts by mass), and 0.1 to 20 parts by mass of an unmodified polyolefin wax (C) per 100 parts by mass of the total amount of (A) + (B), The thermoplastic resin composition, wherein the metal oxide (B) comprises magnesium oxide.
2. The thermoplastic resin composition according to claim 1, wherein the thermoplastic resin (A) is at least one selected from the group consisting of an ethylene-based polymer, a propylene-based polymer, a 1-butene-based polymer, a 4-methyl-1-pentene-based polymer, and an ABS-based resin.
3. The thermoplastic resin composition according to claim 1, wherein the average particle size of the metal oxide (B) is in the range of 0.1 to 110 μm.
4. The thermoplastic resin composition according to claim 1, wherein the thermal conductivity of the metal oxide (B) is in the range of 10 to 300 W / mK.
5. The thermoplastic resin composition according to claim 1, wherein the thermal conductivity of the thermoplastic resin composition is in the range of 0.5 to 5 W / mK.
6. The thermoplastic resin composition according to claim 1, wherein the specific gravity of the thermoplastic resin composition is in the range of 1.0 to 5.
0.
7. The thermoplastic resin composition according to claim 1, comprising 10 to 30 parts by mass of the thermoplastic resin (A) and 70 to 90 parts by mass of the metal oxide (B) (wherein the total amount of (A) + (B) is 100 parts by mass).
8. The thermoplastic resin composition according to claim 1, wherein in an antibacterial test conducted using Escherichia coli in accordance with JIS Z 2801:2012 (film adhesion method), the antibacterial activity value after 24 hours under conditions without water resistance and light resistance pretreatment is 2.0 or more.
9. The thermoplastic resin composition according to claim 1, wherein in an antibacterial test conducted using Staphylococcus aureus in accordance with JIS Z 2801:2012 (film adhesion method), the antibacterial activity value after 24 hours under conditions without water resistance and light resistance pretreatment is 2.0 or more.
10. The thermoplastic resin composition according to claim 1, having an antiviral activity value of 2.0 or more in an antiviral test performed using feline calicivirus in accordance with ISO 21702:2019.
11. The thermoplastic resin composition according to claim 1, comprising a fibrous filler (D) in an amount of 0.1 to 20 parts by mass per 100 parts by mass of the total of the thermoplastic resin (A) and the metal oxide (B).
12. A molded article comprising the thermoplastic resin composition according to any one of claims 1 to 11.
13. A door handle, door knob, handrail or switch comprising the thermoplastic resin composition according to any one of claims 1 to 11.
14. A housing comprising the thermoplastic resin composition according to any one of claims 1 to 11.
15. A clothing accessory comprising the thermoplastic resin composition according to any one of claims 1 to 11.
16. A container comprising the thermoplastic resin composition according to any one of claims 1 to 11.
17. A stationery item comprising the thermoplastic resin composition according to any one of claims 1 to 11.
18. A tableware or sake bottle comprising the thermoplastic resin composition according to any one of claims 1 to 11.
19. A mouse or keyboard comprising the thermoplastic resin composition according to any one of claims 1 to 11.
Citation Information
Patent Citations
Method for preventing sagging of polyolefin sheets
JP1977015542A
Coloring composition for synthetic resin
JP1985096622A
Flame-retardant polyolefin resin foam
JP1997048870A
Colored resin composition for liquid bleaching agent container
JP1997137004A
Colored resin composition for liquid bleaching agent container
JP1997137005A
